Dinamika Masalah Kesehatan Gigi dan Mulut di Indonesia - Lyra Thania; Nur Fatimah; Marniati Marniati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Dental and oral health issues in Indonesia remain a critical concern, with a high prevalence, particularly in dental caries and periodontal diseases. Based on data from Riskesdas 2018 and the 2023 Indonesian Health Survey, more than 50% of the population suffer from caries, with the highest rates found among children and the elderly. This literature review aims to identify the characteristics of oral health problems, risk factors, health and socioeconomic impacts, and the intervention strategies implemented in Indonesia. The study employs a narrative review method by analyzing national publications from 2015 to 2025 that meet inclusion criteria. The findings reveal that the main determinants include low oral health literacy, high sugar consumption patterns, limited access to dental services, and socioeconomic factors such as education and income. The impacts include decreased quality of life, reduced work productivity, and increased burden on the healthcare system. Effective prevention and control strategies involve school- and community-based health promotion, the use of technology such as teledentistry and mobile applications, improvement in basic service access, as well as regulatory policies on sugar consumption and incentives for healthcare personnel in remote areas. Multisector collaboration and continuous research are essential to significantly reduce the burden of oral diseases in Indonesia.